(untitled) (Journal of Asian Development Studies, 2018)
Poverty is out of control in the rural areas of the Pakistan, where people are in a state of deprivation with regards to incomes, clothing, housing, health care and education facilities. According to economics survey 2009-10, 60 percent of the population of Pakistan living in rural areas and is directly or indirectly depends on agriculture for their income. Agriculture sector of Pakistan contributes in GDP is approximately 22 percent while it provides employment at least 45 percent of the total population. The study analyzed the impact of agriculture growth on poverty reduction in Pakistan extracting 31 time series annually observations. The study employed Johansen co integration methodology to test for the existence of a long run relationship between variables. The study concluded that agriculture growth, Employment in Agriculture, GDP, and Trade Openness has negative and significant impact on poverty in long run. To alleviate poverty, it is suggested that Pakistan enhance the productivity of the agriculture sector through the provision of a series of inputs including provision of easy credit to the small farmer, availability of quality fertilizers, pesticides, and by farmer education.